QSAR Study of 17β-HSD3 Inhibitors Using MLR as a Target Receptor for the Treatment of Prostate Cancer - سنوقة, حبيبة (Université of eloued جامعة الوادي, 2025)
علاجيًا في علاج سرطان البروستاتا .تم حساب الوصفات الجزيئية باستخدام ،DRAGONوHyperChem وGaussian09 عبر برامجDFT/B3LYP/6-31G(d) طريقة إلى جانب قاعدة بيانات .SwissADME اعتمدت الدراسة على الانحدار الخطي المتعدد ) (MLRلبناء النموذج، حيث تم تقسيم البيانات إلى مجموعة تدريب واختبار، كما تم استخدام التحقق المتقاطع ) (LOO-CVضمن التقييم الإحصائي. يتكون النموذج من أربعة واصفات جزيئية، وحقق أدا ًء جيدًا من خلال القيم الإحصائية%R²adj ،: R² = 71.1 % ،s = 0.6196 ،Q²LOO = 53.66% ،= 65.3و ،F = 12.3ما يدل على موثوقية النموذج. كما تضمنت الدراسة تقييم الخصائص الحركية الدوائية )(ADMEللمركبات، بما يشمل الامتصاص، التوزيع، الأيض، والإطراح، من خلال تحليل التشبه بالأدوية، الامتصاص المعوي ) ،(HIAوالنفاذية عبر الحاجز الدموي الدماغي) ، (BBBمما يعزز من قيمة النموذج في التنبؤ بفعالية المركبات الدوائية الجديدة This study aims to develop a QSAR (Quantitative Structure–Activity Relationship) model to predict the biological activity of 17β-HSD3 enzyme inhibitors, which are considered a therapeutic target in the treatment of prostate cancer. Molecular descriptors were calculated using the DFT/B3LYP/6-31G(d) method through Gaussian09, HyperChem, and DRAGON software, in addition to the SwissADME database. The study employed Multiple Linear Regression (MLR) to build the model, dividing the data into training and test sets. Leave-One-Out Cross-Validation (LOO- CV) was used as part of the statistical evaluation. The final model consists of four molecular descriptors and demonstrated good performance based on the following statistical parameters: R2 = 71.1%, R2adj = 65.3%, Q2LOO = 53.66%, s = 0.6196, and F = 12.3, indicating the model’s reliability. The study also included the evaluation of the pharmacokinetic properties (ADME) of the compounds, including absorption, distribution, metabolism, and excretion, through analysis of drug-likeness, human intestinal absorption (HIA), and blood–brain barrier (BBB) permeability. This enhances the model’s value in predicting the effectiveness of novel drug candidates.
كيمياء عضوية
Keywords: ADME. ،MLR ،البروستاتا سرطان ،17β-HSD3 ،: QSARالمفتاحية; QSAR; 17β-HSD3; prostate cancer; MLR; ADME.